Professional benefits perception among pediatric nurses: a cross-sectional survey - Wang, Jia; Wang, Hui; Chen, Xiuli; Sheng, Yu (Frontiers in Pediatrics, 2025)
BackgroundThe perception of professional benefits is a critical determinant of job stability and work efficacy among healthcare professionals. This perception can directly influence patient care quality, nurse job satisfaction and retention, as well as overall organizational efficiency. The current understanding of how pediatric nurses perceive their professional benefits is limited. This study aimed to elucidate the status and determinants of professional benefit perception among pediatric nurses to inform evidence-based clinical care.MethodsWe conducted a survey of pediatric nurses at our hospital from September 1, 2024, to November 26, 2024. Participants were selected using a convenience sampling method. The Nurses' Professional benefit perception Scale was employed to assess professional benefit perception. Pearson correlation and multiple linear regression analyses were utilized to identify factors influencing professional benefit perception. These statistical methods were chosen due to their suitability for examining relationships between continuous variables and for controlling potential confounding factors in the regression model.ResultsA total of 366 pediatric nurses participated in the study. The mean score of professional benefit perception was (108.26 ± 17.32). Pearson correlation analysis revealed significant positive associations between professional benefit perception scores and several demographic and professional variables. Specifically, age (r = 0.517), years of experience in pediatric nursing (r = 0.604), educational level (r = 0.564), professional title (r = 0.559), marital status (r = 0.623), and average monthly income (r = 0.647) were all significantly correlated with professional benefit perception scores. Further analysis using multiple linear regression identified these variables as significant predictors of professional benefit perception scores, collectively accounting for 57.20% of the variance (R² = 0.572). This indicates that a substantial portion of the variation in professional benefit perception can be explained by these demographic and professional factors.ConclusionThe perceived level of professional benefits among pediatric nurses is found to be moderate. It is recommended that nursing administrators develop targeted intervention strategies based on the identified influencing factors. Such strategies may include enhancing professional development opportunities, improving financial compensation, and fostering a supportive work environment.